Financial inclusion, financial literacy, and financial education in Azerbaijan - Gubad Ibadoghlu (Asian Development Bank Institute (ADBI), 2018)
This paper discusses the status of financial inclusion, education, and literacy in Azerbaijan as well as measures to foster the development of SMEs, which currently have inadequate access to financial resources. The primary policy challenge faced by the government of Azerbaijan is defining its role in creating broader access to financial products and services. This paper highlights the challenges faced in overcoming the barriers to financial inclusion, and solutions found, and discusses the main lessons learned and a potential way forward. The first section of the paper provides detailed information on the national financial system. The second section covers the status of financial inclusion for individuals and SMEs. The third section analyzes different (supply and demand) aspects of barriers to financial inclusion, while the remaining sections present policies aimed at promoting financial regulation, literacy, and education. Finally, the paper presents key policy recommendations.
Keywords: D14; D18; G21; G28; I28; 330; financial inclusion; financial education; financial literacy; SME; household; Azerbaijan